Desain Pembelajaran Scaffolding Berorientasi Cognitive Perturbation Pada Perkuliahan Statistika Penelitian Pendidikan Sains - Rendy Wikrama Wardana; Afrizal Mayub (Jurnal Pendidikan Matematika Raflesia, 2022)
Abstract The purpose this research was depelove learning design products scaffolding oriented cognitive perturbation and obtaining data on student responses. This research was a development research with ADDIE design (Analysis, Design, Develop, Implementation and Evaluation). Research limited development stage. The research sample was 19 students of Master of Science education at a state university in Bengkulu City. The research instrument was on the form design and material expert validation questionnaire, as well as a student response questionnaire to the developed learning design. Data was collected by giving validation questionnaires to 4 expert lecturers in the field of statistical design and material. Data analysis used quantitative data analysis with descriptive statistics which were then narrated qualitatively. The results showed learning design was categorized as very feasible from the design and material aspects with a percentage of 95.03%. Based on students' responses to the learning design that was developed based on aspects of the learning process and benefits, the average percentage scores were 95.57% and 93%, respectively. These results indicate that the learning design developed can be an alternative solution in the learning process during the COVID-19 pandemic.